Management of Stress: From the Perspectives of the Natural Theory Philosophers - Bubu, Ncha Gabriel (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The phenomenon of stress among humans, has become a disturbing one and a source of worry and sorrow for millions of people all over the world. This, in most cases, has resulted in deaths, strokes and paralysis, and if these occur with individuals that are bread winners in families, the consequences could be devastating as members of such families who are dependent on the bread winners would be put into untold hardship which could result in further stress related problems. One important cause of this phenomenon is poor management of stress and the lack of a suitable stress management strategy. This paper examines this phenomenon and argues that the natural theorist approach could be therapeutic. The method adopted is expository and content analysis.